Investigasi Revisit Intention Pelanggan Restoran Ayam Cepat Saji asal Amerika - Agnes Niela; Aliffiya Nur Oktafianie Sanusi; Alifya Yuniar; Dafara Nur TsaniFitria; Usep Suhud (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
This study aims to the factors that affect revisit intention consumers in American fast food restaurant. In this study, using five variables used to measure, that is convenience, consumers interaction, satisfaction, perceived value and revisit intention. Data collection was conducted in Jakarta during April-May 2020. Data were collected using an online questionnaire and respondents were selected using convenience sampling techniques. Total respondents in this study were 250 respondents as much as 92 men and 158 women who had visited American fast food restaurants. Data were processed using exploratory factor analysis and structural equation models. The results showed that the convenience and consumer interaction variables had positive and significant effects. Variable satisfaction and perceived value affect revisit intention positively and significantly. The revisit intention variable has no positive and significant effect on convenience. Therefore can be concluded that the variable satisfaction, perceived value and consumer interaction affect revisit intention.